Judge appointing procurator in marriage nullity case: Canons 1481, 1592 and 1620 - Morrisey, Francis G. (Roman replies and CLSA advisory opinions 1995, 1995)
Can a judge appoint a procurator in a marriage nullity case for a respondent who cannot be located? Can he do so in the case of a respondent who is extremely hostile?